Length Weight Relationship of Bigeye Scad (Selar crumenophthalmus) Catch by Purse Seine in Manado Bay - Makarondong, Geral Manuel; Sitanggang, Effendi P.; Labaro, Ivor L.; Luasunaung, Alfret; Manoppo, Lefrand; Pangalila, Fransisco P. T.; Thamin, Arman (Sam Ratulangi University, 2022)
The intensity of the catch of bigeye scad (Selar crumenophthalmus), is expected to cause problems in the availability of these fish resources. The purpose of this research is to analyze the Length-weight relationship of Bigeye scad caught by purse seine in Manado Bay. as well as to evaluate the results of the analysis of the Length-weight relationship and the catchment feasibility of the catch to support the sustainability of the potential of bigeye scad resources. The method used in this study is a quantitative method. conducted at Tumumpa Manado Coastal Fisheries Port, using fork length measurement data (FL) and weight of bigeye scad taken by the author under the guidance of lecturers in May 2021 and November 2021. Length-weight relationship of bigeye scad caught in May 2021 follows the equation W = 0,0249 L2.8057 with K = 1.01 and in November 2021 W = 0,0207 L2.9151. The type of bigeye scad in both seasons is categorized as negative allometric. This fish is categorized as unfit to catch (Lc < Lm). The structure of the catch in May 2021 obtained an average length of 10.26 ± 0.26 cm and an average weight of 18.03 ± 1.51 g where 51% were caught at a size of 9.8-10.8 cm and 46% had a weight of 11.0-16.0 g. while in November 2021 the average length was 10.90 ± 0.28 cm and the average weight was 22.53 ± 1.76 g where 50% were caught at a size of 10.0-11.0 cm and 31% g weight 21.0-26.0 g.Keywords: Bigeye Scad; Length Weight Relationship; Decent Catch; Purse Sein; Manado BayAbstrakIkan Selar bentong memiliki cita rasa enak, disukai masyarakat, dan harganya pun murah. Intensitas ketertangkapan jenis ikan ini, diduga kelak akan menimbulkan masalah ketersediaan sumberdaya ikan ini. Tujuan penelitian ini menganalisis hubungan panjang berat ikan selar bentong hasil tangkapan kapal pukat cincin (purse seiners) di Teluk Manado, serta Mengevaluasi hasil analisis hubungan panjang berat ikan selar bentong dengan kelayakan tangkap hasil tangkapan untuk menopang keberlanjutan potensi sumberdaya ikan selar bentong ini. Metode yang digunakan pada penelitian ini yaitu metode kuantitatif, dilakukan di Pelabuhan Perikanan Pantai (PPP) Tumumpa Manado, dengan menggunakan data ukuran panjang cagak (fork length, FL) dan berat ikan selar bentong yang diambil oleh penulis di bawah bimbingan dosen pada Mei 2021 (musim Pancaroba I) dan November 2021 (musim Pancaroba II) yang tertangkap purse seiners di Teluk Manado. Hubungan panjang berat ikan selar bentong yang tertangkap pada Mei 2021 mengikuti persamaan W = 0,0249 L2.8057 dengan K = 1.01 dan pada November 2021 W = 0,0207 L2.9151. Tipe pertumbuhan ikan selar bentong pada kedua musim tersebut terkategori alometrik negatif (b < 3), ikan ini terkategori tidak layak tangkap (Lc < Lm). Struktur hasil tangkapan pada Mei 2021 diperoleh panjang rerata 10.26 ± 0.26 cm dan berat rerata 18.03 ± 1.51 g, di mana 51% tertangkap pada ukuran 9.8 - 10.8 cm dan 46% memiliki berat 11.0-16.0 g, sementara pada November 2021 panjang rerata 10.90 ± 0.28 cm dan berat rerata 22.53 ± 1.76 g, di mana 50% tertangkap pada ukuran 10.0-11.0 cm dan 31% memiliki berat 21.0-26.0 g. Kata Kunci: Selar Bentong; Hubungan Berat Panjang; Kelayakan Tangkap; Pukat Cincin; Teluk Manado